Cyclophosphamide/granulocyte colony-stimulating factor induces hematopoietic stem cells to proliferate prior to mobilization - Morrison, Sean J. (The National Academy of Sciences of the USA, 1997)
We isolated hematopoietic stem cells (HSC) from mice treated with cyclophosphamide (CY) and granulocyte colony-stimulating factor (G-CSF). All mobilized multipotent progenitor activity was contained in two populations: Thy-1(lo)Sca-1(+)Lin(−)Mac-1(−)CD4(−)c-kit(+) long-term reconstituting progenitors and Thy-1(lo)Sca-1(+)Lin(−)Mac-1(lo)CD4(−) transiently reconstituting progenitors. CY/G-CSF treatment drove both long-term and transient multipotent progenitors into cycle, leading to a more than 12-fold expansion in the number of long-term self-renewing HSC prior to mobilization. After CY and 2 days of G-CSF treatment the number of bone marrow HSC began to decline and the number of blood and splenic HSC increased. HSC continued to proliferate in the bone marrow and spleen through 8 days of G-CSF treatment, but HSC released into the blood tended to be in G(0)/G(1) phase. Mobilized multipotent progenitors isolated from the spleen were less efficient than normal bone marrow multipotent progenitors in engrafting irradiated mice but did not differ in colony forming unit-spleen (CFU-S) activity or single cell in vitro assays of primitive progenitor activity. The data suggest that mobilized HSC isolated from the spleen are less efficient at homing to and engrafting the bone marrow of irradiated recipient mice.